THE METHOD OF THE PERFORATED NON-EQUILIBRIUM NUMBERS COMPOSITION - Barannik, V.; Shynkarev, V.; Yudin, A. (Science-based technologies, 2010)
A ground and basic design of the composition assembling times method is expounded non-equilibriumperforation of position numbers on the basis of arrays lower range and overhead the differentiated range levels. Differential description of arrays is built overhead of level perforation, taking into account the presence of dynamic ranges homogeneous structure of overfalls on the scopes of contour and basic background of image. Shown, that composition perforation of number in a difference from non-equilibrium position numbers possesses properties for the potential increase of compression degree.